The Chronicles of Satiation as Reflected on Ryunosuke Akutagawa’s Imogayu - Listyaningsih Listyaningsih; Rommel Utungga Pasopati; Mohammad Mirza (Pioneer: Journal of Language and Literature, 2022)
Literature examines differences among classes especially the powerful-the non-powerful and the rich-the poor through literary conditions. Imogayu is Ryunosuke Akutagawa’s short story that tells Goi, a poor samurai. He is astonished with imogayu (yam gruel) and wishes more of it, but his fellows and master laugh at him for wishing so. The master asks Goi to follow him eat more imogayu and he agrees. In a village, his master tells his servants to cook imogayu then tells Goi to eat. Seeing many people cooked it then looking at plentiful imogayu, he loses appetite as he is fed up. Thus, the research question is, how is satiation reflected on Ryunosuke Akutagawa’s Imogayu? Through qualitative method on economic, socio-political, and psychological points, this study underlines changing condition of Goi from wanting imogayu to becoming satiated. Through psychology of satiation by Jeff Galak, behavior could change when consumption face hedonistic enjoyment. Class difference is seen in how Goi’s wish does come true but its abundant amount makes him sick of seeing wasted material used. In conclusion, Goi’s satiation comes from how his simple wish faces lavish reality. His satisfaction changes into satiation after seeing luxury that he never senses at all.